2015
DOI: 10.1093/jxb/erv496
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 CYP71BE5 in grapevine (Vitis vinifera) catalyzes the formation of the spicy aroma compound (−)-rotundone

Abstract: HighlightCYP71BE5 from grapevine was identified as a sesquiterpene oxidase capable of transforming α-guaiene to (−)-rotundone, responsible for the characteristic spicy aroma in wines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 66 publications
(89 reference statements)
2
45
0
1
Order By: Relevance
“…In 2014, the technique did not impact significantly the rotundone concentration and more variability was observed within the data set. The cutting of the fruit bearing cane seems to have slowed down the accumulation of rotundone which can be formed by direct synthesis from ␣-Guaiene (Takase et al, 2016) or accelerated its degradation in Cane in 2013 without this being observed in 2014. Mechanisms involved appear to be complex and rotundone concentration in experimental wines is the resultant of both accumulation and degradationin the berries.…”
Section: Parametermentioning
confidence: 99%
“…In 2014, the technique did not impact significantly the rotundone concentration and more variability was observed within the data set. The cutting of the fruit bearing cane seems to have slowed down the accumulation of rotundone which can be formed by direct synthesis from ␣-Guaiene (Takase et al, 2016) or accelerated its degradation in Cane in 2013 without this being observed in 2014. Mechanisms involved appear to be complex and rotundone concentration in experimental wines is the resultant of both accumulation and degradationin the berries.…”
Section: Parametermentioning
confidence: 99%
“…Meanwhile, an analysis of wines produced from this vineyard over 15 vintages showed that the highest concentration of rotundone was found in wines from cool and wet seasons (Zhang et al ). Whilst other work has started to unravel the genetic elements of the biosynthesis of rotundone (Drew et al , Takase et al ), the question of how this understanding might be applied to the advantage of grapegrowers and winemakers remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the mechanism for forming a 12,6b-lactone at the germacrene stage in thapsigargin biosynthesis has been described (Andersen et al, 2017), in which a 6b-hydroxyl group is already present prior to the successive oxidation on the C12, and then the C12 triple oxidation leads to the spontaneous formation of a 12,6blactone ring. Therefore, similarly, to form the 12,8b-lactone ring, it would be possible that the 8b-hydroxylation on germacrene A might occur before the C12 triple oxidation by the GAO, as the enzyme GAO catalyzing the C12 triple oxidation has a broad substrate specificity (Gavira et al, 2013;Eljounaidi et al, 2014;Takase et al, 2016), and may accommodate the 8b-hydroxyl germacrene A as the substrate to facilitate the 12,8b-lactone ring formation. However the co-expression of CYP71BL6 in yeast with the germacrene A synthase LsGAS suggested that CYP71BL6 has no activity with germacrene A (Figure S5).…”
Section: Discussionmentioning
confidence: 99%